Consider the polynomial: $$f=X^4+4X^3+6X^2+aX+b$$ We know that $f$ has four real roots. Let $x_1,x_2,x_3,x_4$ be the roots of this polynomial. How can one compute $$x_1^{2015}+x_2^{2015}+x_3^{2015}+x_4^{2015}?$$ If $a=4$ and $b=1$, we obtain a self-reciprocal (palindromic) polynomial. We can write $f=(X+1)^4$, thus $x_1=x_2=x_3=x_4=1$. Hence the sum computes to $-4$. Are there any other cases to consider ($a,b$)? I thought using the formula for the quartic equation and paying attention to the cases where we have only real roots. Any ideas? Thank you!

  • $\begingroup$ Note that in case $a=4, b=1$ you don't obtain $f=(X-1)^4$ but rather $f=(X+1)^4$ which yields $x_1=x_2=x_3=x_4=-1$ and hence the sum computes to $-4$. $\endgroup$ – Tintarn Aug 26 '15 at 18:24

We know the following to be true:

$$ \tag1x_1+x_2+x_3+x_4 = -4 $$ $$ \tag2x_1x_2+x_2x_3+x_3x_4+x_4x_1+x_1x_3+x_2x_4 = 6 $$ $$ \tag3x_1 x_2x_3+x_2x_3x_4+x_3x_4x_1+x_4x_1x_2 = -a $$ $$ \tag4x_1x_2x_3x_4 = b $$

Now we can square $(1)$ to get

$$ \begin{align} (x_1+x_2+x_3+x_4)^2 = &x^2_1+x^2_2+x^2_3+x^2_4\\ &+2[x_1x_2+x_2x_3+x_3x_4+x_4x_1+x_1+x_3+x_2x_4] \end{align} $$

Substituting in values from $(1)$ gives

$$ \begin{align} (-4)^2 &= x^2_{1}+x^2_{2}+x^2_{3}+x^2_{4}+2(6)\\ 16&=x^2_{1}+x^2_{2}+x^2_{3}+x^2_{4}+12\\ 4&=x^2_{1}+x^2_{2}+x^2_{3}+x^2_{4} \end{align} $$

Using the Cauchy-Schwartz Inequality, we get

$$ \left(x^2_{1}+x^2_{2}+x^2_{3}+x^2_{4}\right)(1^2+1^2+1^2+1^2)\geq (x_{1}+x_{2}+x_{3}+x_{4})^2 $$

where equality holds when

$$ \tag5x_{1} = x_{2} = x_{3} = x_{4} $$

Thus, the equality condition holds, because $4\cdot 4= (-4)^2$. So from $(1)$ and $(5)$, we have $$x_{1} = x_{2} = x_{3} = x_{4}=-1$$

Setting the values of $x_{1} = x_{2} = x_{3} = x_{4}=-1$ in $(3)$ and $(4)$, we get $(a,b)=(4,1)$, which is thus the unique solution. So we can evaluate the sum as

$$ \begin{align} x^{2015}_{1}+x^{2015}_{2}+x^{2015}_{3}+x^{2015}_{4} &= (-1)+(-1)+(-1)+(-1)\\ &=-4 \end{align} $$


Note that $x_1+x_2+x_3+x_4=-4$ since $f=(X-x_1)(X-x_2)(X-x_3)(X-x_4)$ and we can just compare the coefficient of $X^3$. We can use this idea to get larger powers. Similarly we can get $x_1^2+x_2^2+x_3^2+x_4^2=16-(2\times 6)=4$ and use a similar trick for cubes.

Define $Tr(x_1^i)=x_1^i+x_2^i+x_3^i+x_4^i$. This function has a deeper meaning, but all we shall use from it is that is additive, ie $Tr(a+b)=Tr(a)+Tr(b)$, which you are welcome to prove if you wish.

Now for higher powers we note that $x_1^4=-4x_1^3-6x_1^2-ax_1-b$ hence using this identity we can write $x_1^{2015}$ in the form $Ax_1^3+Bx_1^2+Cx_1+D$ and use the additive property of the trace function $Tr$ I defined above and the values we worked out for these to get an exact answer.

  • $\begingroup$ Meaning of the $Tr$ function is not clear to me. Is it $Tr(x) = x + a + b + c$, where $x$ is an argument and $a,b,c$ are parameters? $\endgroup$ – Kaster Aug 26 '15 at 18:41
  • $\begingroup$ If you plug a root $\alpha$ of $f$ in then $Tr(\alpha^i)$ gives you the sum of the roots to the same power and the additive property allows you to extend this to a full definition. Technically it is the sum of all the galois conjugates of an element over the field extension if you understand that. $\endgroup$ – Matt B Aug 26 '15 at 18:44
  • $\begingroup$ Is it a function of the root, or root in the power of $i$, or all roots? $\endgroup$ – Kaster Aug 26 '15 at 18:46
  • $\begingroup$ When we adjoin all the roots of the polynomial to our field $\mathbb{Q}$, we get a new field $K$, and then $Tr:K \rightarrow \mathbb{Q}$ as a function. $\endgroup$ – Matt B Aug 26 '15 at 18:48
  • $\begingroup$ So in particular, it is a function on any $\mathbb{Q}$-linear combination of the roots and their powers. $\endgroup$ – Matt B Aug 26 '15 at 18:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.